A Comparison of the Predictive Validity of Self-Esteem Level and Directly Measured Self-Esteem Stability in the Temporal Prediction of Psychological Distress - Roth, Marcus; Altmann, Tobias (Frontiers in Psychology, 2020)
In contrast to the widely used assessment approach in which self-esteem stability is measured as the standard deviation of repeated measurements, direct measurements of self-esteem stability have hardly ever been implemented in longitudinal studies. The primary goal of the present study was to examine the temporal stability and predictive validity of a direct assessment of self-esteem stability compared with the trait level of self-esteem with respect to the prediction of psychological distress. We examined a sample of 136 employees who completed self-report measures of both self-esteem level (RSES) and self-esteem stability (SESS) along with a measure of psychological distress (SCL-90) at two time points across an interval of 1 year. The results underline the relevance of perceived self-esteem stability in the temporal prediction of psychological distress: After controlling for initial psychological distress, we found that self-esteem stability predicted psychological distress better than self-esteem level did. Therefore, we recommend that the Rosenberg Self-Esteem Scale be expanded by adding the three SESS items that directly measure the stability of self-esteem.